2008
DOI: 10.1037/h0099345
|View full text |Cite
|
Sign up to set email alerts
|

Hook-up behavior: A biopsychosocial perspective.

Abstract: Hook-up behavior consists of sexual activity between uncommitted individuals. "Hooking up" has become pervasive among young adults, particularly on college campuses in the United States, despite inherent emotional, physical, social and health risks. A total of 507 undergraduate students were surveyed to assess the prevalence of, and motivations for, hook-up behavior. Of those students, 64% reported having ever engaged in a hook-up. Of those who had hooked up, 51% had done so with the intention of initiating a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
211
5
6

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(251 citation statements)
references
References 39 publications
14
211
5
6
Order By: Relevance
“…Similar to Garcia and Reiber (2008) and Townsend et al (2015), we found no sex differences in the number of sex partners in the last 12 months. However, we did find men engaged in more one night stands and had more casual sexual partners (no time frame specified).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Similar to Garcia and Reiber (2008) and Townsend et al (2015), we found no sex differences in the number of sex partners in the last 12 months. However, we did find men engaged in more one night stands and had more casual sexual partners (no time frame specified).…”
Section: Discussionsupporting
confidence: 54%
“…The differences between these measures of casual sex could be due to several factors. Garcia and Reiber (2008) reported no sex difference in hooking up in the past year among college students but more men reported sex with strangers and more women reported sex with traditional romantic partners. Our sample could have varied in their answers to the casual sex questions because of variations in behavior prior to college, as we had many first year students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…El alcohol, elemento desinhibidor y reforzador de las expectativas sexuales, puede favorecer la inclinación a participar en conductas sexuales íntimas con un amigo, constituyendo una conducta de riesgo vinculada a la asunción de otros peligros en el campo de la salud sexual (Afifi;Faulkner, 2000;Weaver;MacKeigan;MacDonald, 2011). En este sentido, es más probable que se produzca el sexo casual cuando ambas partes han estado bebiendo o consumiendo drogas (García;Reiber, 2008;Grello;Welsh;Harper, 2006). Por tanto, se puede afirmar que el consumo de alcohol está relacionado con la participación en una relación de AMB precediendo a la mayoría de las conexiones sexuales (Fielder;Carey, 2010).…”
Section: Introductionunclassified